Negosiasi Kepentingan Dalam Perumusan RPJMD DIY 2017-2022 Dalam Kerangka Advocacy Coalition Framework: Negotiation of Interest in RPJMD DIY 2017-2022 Policy Formulation Using Advocacy Coalition Framework - Kamim, Anggalih B.M; Amal, Ichlasul; Khandiq, M. Rusmul (Pusjar SKPP Lembaga Administrasi Negara, 2019)
An exploration of policy changes and learning and interest negotiation in formulating policy are useful for mapping the process of compromising between the authorities and citizens. The study aims to explore the relations of external actors and local governments as a reflection of the state in the formulation of 2017-2022 DIY development planning policies to ensure no policies that favor the interests of certain groups. This research was conducted in qualitative research methods. This research was framed by a case study method. The research was conducted in agencies/ companies/ academics/ donor institutions/ parliament and the community involved and affected in the process of formulating DIY development planning policies. Research showed that there were some disadvantages of ACF model. The first disadvantage related to the inability of the ACF to explain the position of one of the